Influence of Interferon alpha-2a Treatment on Monocyte Subsets in Patients with Uveitis - DİRESKENELİ, RAFİ HANER (TURKISH SOC IMMUNOLOGY, 2020)
Introduction: Interferon alpha is a type-I interferon molecule with antiviral and antineoplastic properties. Interferon a treatment is also used in the management of uveitis and believed to have immunomodulatory properties demonstrated by increased number of regulatory T cells. The aim of this study was to define the influence of interferon alpha-2a treatment on monocyte subsets in patients with uveitis. Materials and Methods: Six patients with uveitis and 7 healthy control subjects were included in this study. Blood samples were obtained from the uveitis patients before treatment with interferon alpha-2a and at the 1st month of treatment (or at clinical remission). Peripheral blood mononuclear cells were stained with anti-CD16, anti-CD14, anti-PD-1, anti-CTLA-4, anti-LAG-3, anti-TIM-3 and anti-TIGIT antibodies and analyzed with flow cytometry. Data were analyzed with FlowJo software and statistical analysis was performed with SPSS 21.0 software. Results: Six patients with uveitis (5 Behcet's, 1 Eales disease, mean age: 29.0 +/- 3.8 years, 4 male, 2 female) and 7 healthy control subjects (mean age: 28.4 +/- 4.9 years, 3 male, 4 female) were included. The number of CD14+CD16-classical monocytes were increased and CD16+ non-classical monocytes were decreased in patients with active uveitis compared to controls (p=0.037 and p=0.045) and this difference disappeared after treatment with interferon a-2a. There was no difference in immune checkpoint receptor expressions between groups at baseline. PD-1 expression increased significantly after interferon alpha-2a treatment (p=0.01). Conclusion: Interferon alpha-2a treatment increases the ratio of non-classical monocytes and their expression of PD-1. These changes may be associated with the previously demonstrated immunomodulatory effects of interferon alpha-2a in patients with uveitis.
Keywords: Monocyte; Behcet's disease; uveitis; interferon alpha; PD-1; ADALIMUMAB; ACTIVATION; EFFICACY; THERAPY; SAFETY; CELLS